INTRODUKSI PAKAN SILASE PADA PETERNAKAN DI UKM KARYA BERSATU DAN PONDOK PESANTREN DARUSSALAM KAMPUNG AIMASI - A. Supriyantono; Budi Santoso (Fakultas Peternakan Universitas Papua, 2010)
Introduce of silage was done at farmers group of small and middle entrepreneur of Karya Bersatu and Darussalam Islamic Centre. The aims were to obtain proper, cheap and safe technology package based on local circumstance. To guide farmers applying paddy wastes as high quality livestock diet and providing continuity of diet when entering dry season. The program was performed for seven months using extension and two-way discussions; guiding famers In making silage made of paddy wastes were chosen as plot demonstration. The result shown that there were changes of attitude of fanners in using silage diet. Understanding of materials were one indicator shown during discussions. Members of farmer group was enthusiastic. They were actively involved in collecting paddy wastes, cutting and mixing with onggok and tofu wastes, and spraying it with starter of lactic acid bacteria, pressing silage material into silo and placing silo into save room.